Legal regulation of the Ukrainian national ecological network formation as the component of European ecological network - Гольонко, Руслан Анатолійович (Problems of legality, 2016)
Formation of the national ecological network is of fundamental importance for the conservation of biological and landscape diversity and creating a system of territories with natural conditions of landscape and other natural complexes and unique areas. Ukraine states that one its main aims is the gradual approximation of national legislation to the law and policy of the European Union. The author points out that for the further development of the Ukrainian national ecological network in the context of the European ecological network, it is necessary to: establish the habitat concept of the ecological network formation; improve the management mechanism of ecological network; introduce the principles and criteria for selecting components of the ecological network and EU standards of biological and landscape diversity. After the adoption of the relevant lists of species and habitat types, it is proposed to enshrine in the Ukrainian legislation among many possible scientifically based criteria of selecting territories under special protection, the following: 1) representativeness degree of the type of natural habitat on this territory; 2) quantity (size) and population species density, which is represented within the territory, in comparison to the size and density of population of the same species at the country level; 3) degree of preservation of the outstanding habitats characteristics that are important for the valid species and for their ability for self-regeneration; 4) total area of the territory; 5) global ecological value of the territory for a biogeographic region and / or for the entire territory on a specific or unique aspect of its features and their combinations.